Ação educativa em museus para o ensino e aprendizagem de alunos do ensino médio do Centro de Ensino (C.E) Odolfo Medeiros, Caxias-MA - FERREIRA, Nilson Gomes (2023)
The research deals with educational actions in museums for the teaching and learning of high school students to be used in the pedagogical practices of teachers of history and related areas. The research space was a state school in the city of Caxias, entitled: "Centro de Ensino (C. E.) Odolfo Medeiros". The general objective of the research was "To investigate the role of the Balaiada Memorial School Museum in the context of high school with a view to producing a Pedagogical Manual containing innovative teaching practices". The central problem of the research was to answer "How can a Pedagogical Manual, containing a set of pedagogical actions about the Memorial School Museum of Balaiada, contribute to the development of teaching and learning strategies?" The Dissertation is divided into three parts, namely: bibliographical, empirical and the description of the Pedagogical Manual. The bibliography describes and substantiates the sections on Museums and their pedagogical implications. In the empirical part, we discuss the characterization of the Teaching Center (C. E.) Odolfo Medeiros, the method and methodology of the research, the analyses and interpretations of the participants. Then, we presented the proposal of the educational product, through the Pedagogical Manual, called: Educational Action in Museums for high school students. The Handbook is composed of six thematic units for teacher guidance. Due to Covid-19, the application of the product in the selected school was discarded. In this sense, we follow Normative Instruction No. 04/2020/PPGEEB/UFMA, which allows the application of the product. The main bibliographic references used were: Sousa (2020), Lucky (2009), Tolentino (2012), and Mota (2012), among others. The data collection instruments used were systematic observation and semi-structured interviews with the school manager and two teachers of the 1st year of high school, morning and afternoon. We discovered, through the research, that the Pedagogical Manual, based on educational actions about museums, contributes to teachers to develop innovative teaching practices.